Effect of cooperative directed reading on the writing performance of ESL undergraduate students - Ahour, Touran (2010)
The aim of the present study was to investigate the effect of cooperative directed reading (CDR) on the writing performance of ESL students. A quasi-experimental research with non-equivalent control group pretest-posttest design was employed. Three intact classes of freshman students taking the expository writing course were used as the sample (N=102) of the study for the duration of one semester. The classes were randomly assigned into Cooperative Directed Reading (CDR) (n=41), Directed Reading without Cooperation (DR-C) (n=40), and No Treatment (NT) (n=21) groups. Two writing samples on two different but comparable expository writing prompts were collected from the groups at the pretest. Then, two main strategies of Cooperative Reading Circles (CRCs) with discussion roles and KWLH (what I know about the topic - what I want to know- what I have learned- how I can learn more) strategy were used in CDR group, while only KWLH strategy was employed in DR-C group. The No Treatment group had only their regular expository writing course activities. At the end of the program, the students were tested on the same writing prompts as the pretest in order to find out the effect of the experiments on the writing performance of the students in two conditions when the writing prompt was thematically related to the reading topic and when it was thematically unrelated. For evaluating the writing samples of the students two assessment methods were employed: (1) An analytical scoring scale as the subjective measure for evaluating the seven dimensions of writing (i.e., content, organization, cohesion, vocabulary, grammar, punctuation, spelling), as well as fluency, accuracy, and overall writing performance of the students; (2) T-Unit count as the objective measure for assessing the writing fluency, based on Mean T-Unit Length (MTUL), and writing accuracy, based on Mean Error-Free T-Unit Length (MEFTU). In addition, a qualitative analysis of thought processes of students in CDR group was carried out, based on CRCs’ discussion transcripts and their written worksheets during the treatment, to show the effect of reading and discussion on the promotion of students’ critical and creative thinking which would influence their writing performance. The results of one-way within-subjects (repeated measures) ANOVA and one-way multivariate analysis of covariance (MANCOVA) revealed that the CDR group had statistically more significant results, with medium and large effect sizes, in both conditions of the study compared to the DR-C and NT groups. This implies that adding the element of cooperation to the solitary task of reading can enhance the prerequisite knowledge of the students for writing which in turn can improve their writing quality. The results indicated the priority of using cooperative activities in the writing classes rather than individualistic ones. The findings verified the underlying principles of cooperative learning theory and indirect model of reading for writing as one of the models of reading-writing connection theories.